Video modelling as a tool to evaluate self-perception of strategies used by adolescents during daily tasks. - Zlotnik, Sharon; Gal, Eynat; Weiss, Patrice L. (Disability & Rehabilitation: Assistive Technology, 2022)
Metacognition is defined as the process of regulating behavior and having self-perception of own performance. An application of video modeling (VM) was used as a technological solution for assessing self-perception in daily situations among typical adolescents, compared to parental reports and to an objective performance-based assessment. One hundred and three adolescents (30 boys, 73 girls, mean age =15.1, SD = 1.9), viewed five clusters of videotaped scenarios of teen actors performing daily activities entailing strategy use. Half of the scenarios were classified as "Type A" indicating a more organized approach to accomplishing a task, the other half were "Type B" scenarios indicated a less organized approach to accomplishing the same tasks. Participants were asked to choose the scenarios that best represent their own daily performance using the VM application. The participants then completed the WCPA, an executive function (EF) performance-based assessment. Their parents completed the BRIEF as an indication of EF behaviors in the home environment. 46% of the adolescents associated their performance with a less organized approach yet parental reports indicated adaptive daily performance and their ability to complete the WCPA was as correct as it was for the 56% of participants who associated their performance with a more organized approach. Unexpectedly, the participants who associated their ability as less organized presented successful behaviors in the home environment and successfully performed the WCPA. Therapists should be aware that clients may achieve success in daily tasks even though they may cope with cognitive challenges in unexpected ways. Therapists may expect adolescent clients to approach tasks in a variety of ways, using different strategies for coping with everyday cognitive challenge. Therapists need to acknowledge that there is no ideal strategy that provides a solution for all individuals. Mediating a guided discovery of strategies through use of VM technology may customize intervention for each client's needs, assuring a client-centered approach and may encourage a collaboration of therapists and clients in search for the strategies that work best for them.